Identification of stinging bees (Apis) and stingless bees (Meliponini) in The Air Panas Hapanasan Springs Tourism Area, Rokan Hulu Regency - Mubarrak, Jismi; Dahlia, Dahlia; Sonia, Sonia; Lestari, Rena; Brahmana, Eti Meirina (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2024)
Bees play a crucial role as pollinators, yet they still receive insufficient attention. This research aims to identify the species of stinging bees (Hymenoptera: Apidae: Apis) and stingless bees (Hymenoptera: Apidae: Meliponini) in the Hapanasan Hot Springs Tourism Area, Rambah Tengah Hulu Village, Rokan Hulu District. The study was conducted from January to June 2023 using a survey method with purposive sampling technique for sample collection. Bees collected were identified by describing their morphological characteristics. The stinging bee species identified include Apis cerana. The stingless bee species identified include Tetrigona binghami, Heterotrigona itama, Geniontrigona thoracica, Lepidotrigona terminata, Lisotrigona carpenteri, Tetragonula testaceitersis, Tetragonula laeviceps, Tetragonula fuscobalteata, and Tetragonula clypearis.